2015
DOI: 10.1038/srep18138
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum 25-hydroxyvitamin D and bone turnover markers in a population based sample of German children

Abstract: Severe vitamin D deficiency is known to cause rickets, however epidemiological studies and RCTs did not reveal conclusive associations for other parameters of bone health. In our study, we aimed to investigate the association between serum levels of 25(OH) vitamin D and bone turnover markers in a population-based sample of children. 25(OH)D, calcium (Ca), osteocalcin (OC), and β-Crosslaps (β-CTx) were measured in 2798 ten-year-old children from the German birth cohorts GINIplus and LISAplus. Linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…The crosslaps values were similar to those of healthy French and Italian children of the same age (using the same assay) and the osteocalcin values were comparable with those of healthy Italian and Danish children of the same age (different assays). One study of 2798 10‐year‐old German children showed that 25(OH)D 3 had an inverse seasonal relationship with osteocalcin and crosslaps . Our data show a positive correlation between Δ osteocalcin and crosslaps, and that there was an after‐holiday significant reduction of osteocalcin in the boys compared with an increase in the girls.…”
Section: Discussionsupporting
confidence: 51%
“…The crosslaps values were similar to those of healthy French and Italian children of the same age (using the same assay) and the osteocalcin values were comparable with those of healthy Italian and Danish children of the same age (different assays). One study of 2798 10‐year‐old German children showed that 25(OH)D 3 had an inverse seasonal relationship with osteocalcin and crosslaps . Our data show a positive correlation between Δ osteocalcin and crosslaps, and that there was an after‐holiday significant reduction of osteocalcin in the boys compared with an increase in the girls.…”
Section: Discussionsupporting
confidence: 51%
“…The serum concentration of 25(OH)D is approximately 1,000 times higher than that of 1,25(OH) 2 D. An overview of reported 25(OH)D concentrations from studies in 17 European countries (Spiro and Buttriss, ) and other recent European data ((Thiering et al., ) in Germany) show that mean/median concentrations (Section 2.4.1) range from about 20 to 95 nmol/L in adults or children.…”
Section: Definition/categorymentioning
confidence: 93%
“…This circadian effect can be generally observed with most BTMs, though CTX displays the highest amplitude in circadian variation (24 ). Additionally, seasonal variation is observed in bone turnover, with a peak in bone remodeling occurring during winter months, though the degree of coupling varies with premenopausal women showing the greatest seasonal variation (25 ). Bone resorption levels drop post-prandially, which is a significant contributor to the rise in CTX occurring during the early morning, which is typically the longest period of fasting each day.…”
Section: Preanalytic Factors In the Measurement Of Btmsmentioning
confidence: 99%